Customized Insulation Strategies for Türkiye: Life Cycle Cost Analysis and Impact on Business Competitiveness - Muhammet Saygın; Ekin Can Dolgun; Serkan Say; İsmail Yavuz Öztürk (Buildings)
A significant portion of energy consumption in buildings is allocated to heating, with substantial losses resulting from inadequate insulation, poor sealing, and thermal bridging. While proper insulation plays a crucial role in mitigating these losses, determining its optimal thickness is essential to reduce energy consumption and increase energy efficiency. This study employs life cycle cost analysis and average heating degree day values to calculate the optimum insulation thickness for 81 provinces in Türkiye. The findings highlight the absence of a one-fits-all insulation solution, emphasizing the need for customized approaches tailored to specific conditions that consider specific factors, such as environmental conditions, heating sources, costs, economic parameters and the materials used. Proper insulation application is projected to reduce carbon emissions by 90% and lower annual heating costs by approximately 65%. These energy efficiency improvements are particularly significant for both households and businesses, enhancing profitability and competitiveness. Collaborative efforts to promote proper insulation solutions are anticipated to reallocate financial resources toward innovation and contribute to long-term business sustainability. This study provides an important framework for guiding the adoption of proper insulation practices in building design and construction.